CORD CARE AND ITS ASSOCIATED FACTORS AMONG MOTHERS OF BUWAMBO VILLAGE, WAKISO DISTRICT. A CROSS-SECTIONAL DESCRIPTIVE STUDY. - Lizinde , Allan; Suubi, Mariam (Student's Journal of Health Research Africa, 2023)
Purpose of the study: Cord care is the series of steps applied in the handling of the umbilical cord during and after the delivery of the newborn. Cord care is an educational and comprehensive medical activity that majorly prevents cord sepsis. The objective of the study: To determine factors associated with cord care among mothers of Buwambo village. While the specific objectives were To assess maternal factors, health workers as well as community impact on maternal cord care practices among mothers of Buwambo village. The findings: The majority 83(83%) of the mothers in the study had sufficient knowledge about cord care, 11(11%) of the respondents reported the use of local herbs and other nonmedical substances and 6(6%) had very little knowledge about cord care, 77(77%) of the mothers in the study attended ANC 3 - 4 times, 11(11%) more than 4 times and 12 (12%) mothers attended only 2 times. 85(85%) of the mothers cleaned the cord 3 times a day, 9(9%) cleaned twice and only 6(6%) cleaned more than 3 times a day. 66(66%) of the mothers involved in the study were taught about cord care by a health worker and variations were only in the time of education, 31(31%) were taught by their mothers and elder relatives and only 3(3%) were self-taught. Cultural norms and practices like putting drops of breast milk in the urachus were discussed in the community. Conclusion: Maternal, community as well health workers in contact with the mother play an important role in maternal cord care practices. Recommendation: Mass sensitization of the public should go on to a complete understanding of the recommended cord care practices and their advantages. Any program aimed at creating mass awareness about advised cord care practices at the district level should be boosted by the people in charge